Facies architecture of fluviatile deposits of the jurassic-cretaceous bertangga formation, peninsular malaysia - Baioumy, H. (Gebruder Borntraeger Verlagsbuchhandlung, 2020)
Bertangga Formation is a part of the Jurassic-Cretaceous non-marine sequences in Thailand and Malaysia. However, its facies analysis and depositional model have not been investigated in detail. Eleven lithofacies have been described in the Bertangga Formation and combined five fa-cies associations including channel, point bar, floodplain, crevasse splay and swamp facies asso-ciations. Channel deposits are stacked bodies of fining upward sequences with prevalent erosional bases, formed by vertical aggradation and avulsion of channels. Point bar sands comprise cross bed-ded sandstone bodies formed in upper flow regime and possible lateral accretion surfaces. Crevasse splay deposits form sheets of fine-to-medium-grained sandstone. Floodplain sediments are composed of motteled grey mudstone. Swamp depositional environment is characterized by an association of coal, carbonaceous shale and siltstone. Facies analysis allows reconstruction of the depositional environment of the Bertangga Formation as a meandering fluvial system. Facies association also shows the increasingly distal and fine-grained trend from west to east of the studied area, which suggests possible eastward paleo-flow direction of the river. The existence of kaolinite in all samples indicates weathering of felsic rocks under acidic conditions. In the same time, the presence of smectite in the eastern part of the study area may suggest a contribution of mafic and/or volcanic rocks to the source of sediments in this area. Â© 2020 E. Schweizerbartâsche Verlagsbuchhandlung, Stuttgart, Germany DOI:.